Implementasi Asas Keterbukaan Terhadap Mekanisme Pengesahan Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2022 Tentang Cipta Kerja - Wahyudin Djou; Erman I. Rahim; Abdul Hamid Tome (Lembaga Pengembangan Kinerja Dosen, 2024)
In terms of the ratification of Perppu Number 2 of 2022 concerning Job Creation, this raises pros and cons in society. This is because the Supreme Court Constitutional Decision Number 91 / PUU-XVIII / 2020 states that Law Number 11 of 2020 is unconstitutional conditional and must be immediately revised within 2 (two) years from the time the decision is issued. One of the reasons is because in the formation of the Job Creation Law, it does not involve full community participation and is not guided by the principle of openness. But the government actually responded by issuing the Job Creation Perppu which was later passed into law by the DPR-RI. In fact, between Law Number 11 of 2020 concerning job creation and Perppu Number 2 of 2022 concerning job creation, it is relatively the same in terms of content. This study aims to examine a legal truth related to the mechanism for ratifying Government Regulations in Lieu of Law based on actual legal provisions. One of the legal provisions in the formation of laws and regulations is to make the principle of forming laws and regulations one of the conditions that must exist in the process of forming laws. One of its principles is the principle of openness. and the method used in this study is Normative. And in the results of this study, it shows that the ratification of the Job Creation Perppu is not in accordance with the mechanism for the Establishment of Laws and Regulations because it is not guided by the principle of openness.